Benefits of client/server financials in Singapore an early report card. - Lim, Chong Hong. (2008)
The client/server accounting software, or client/server financials market in the US is currently in an explosive growth period. However in Singapore, client/server accounting software remains relatively new technology for most companies. But it is catching on and companies are either in the final stages of implementation or are exploring seriously the possibility of migrating to this new exciting technology. In this research project we seek to study the issues relating to the adoption of this technology and its impacts or benefits.